2023
DOI: 10.3390/antiox12030624
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Dihydrophenanthrene Derivatives from Dendrobium virgineum with Protective Effects against Hydrogen-Peroxide-Induced Oxidative Stress of Human Retinal Pigment Epithelium ARPE-19 Cells

Abstract: Oxidative stress is a significant factor in the development of age-related macular degeneration (AMD), which results from cell damage, dysfunction, and death in the retinal pigmented epithelium (RPE). The use of natural compounds with antioxidant properties to protect RPE cells from oxidative stress has been explored in Dendrobium, a genus of orchid plants belonging to the family Orchidaceae. Two new compounds and seven known compounds from the MeOH extract of the whole plant of Dendrobium virgineum were succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Although NaIO 3 is not directly involved in AMD pathology, it provides a means to understand the mechanisms of RPE cell death and likely choriocapillaris degeneration as key pathogenic markers of AMD [ 48 ]. Recent studies have shown that NaIO 3 induces oxidative damage and promotes apoptosis in RPE cells [ 59 , 60 ], characterized by decreased cell viability, increased ROS levels, increased expression of pro-apoptotic proteins such as Bax and cleaved caspase-3 [ 61 , 62 , 63 , 64 ], and decreased Bcl-2 expression [ 62 ]. Interestingly, a peptide derived from a highly conserved region of the human lens protein αA-crystallin, known as mini-αA, has a protective effect against NaIO 3 -induced outer retinal degeneration [ 65 , 66 ].…”
Section: The Sodium Iodate (Naio 3 ) Acute Model O...mentioning
confidence: 99%
“…Although NaIO 3 is not directly involved in AMD pathology, it provides a means to understand the mechanisms of RPE cell death and likely choriocapillaris degeneration as key pathogenic markers of AMD [ 48 ]. Recent studies have shown that NaIO 3 induces oxidative damage and promotes apoptosis in RPE cells [ 59 , 60 ], characterized by decreased cell viability, increased ROS levels, increased expression of pro-apoptotic proteins such as Bax and cleaved caspase-3 [ 61 , 62 , 63 , 64 ], and decreased Bcl-2 expression [ 62 ]. Interestingly, a peptide derived from a highly conserved region of the human lens protein αA-crystallin, known as mini-αA, has a protective effect against NaIO 3 -induced outer retinal degeneration [ 65 , 66 ].…”
Section: The Sodium Iodate (Naio 3 ) Acute Model O...mentioning
confidence: 99%
“…In addition, Dendrobium (also known as Shihu) has been also used as an important food ingredient in many dietary supplements such as Shihu wine and Fengdou Shihu [5]. Secondary metabolites from Dendrobium such as flavonoids, bibenzyls, phenanthrenes, alkaloids and sesquiterpenoids have been reported to provide various pharmacological activities, for instance, anti-inflammatory, antioxidant, antiangiogenic, anticancer, antimicrobial, neuroprotective and immunomodulatory activities [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, most of these studies were performed in human cell lines or animal models [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites from Dendrobium such as flavonoids, bibenzyls, phenanthrenes, alkaloids and sesquiterpenoids have been reported to provide various pharmacological activities, for instance, anti-inflammatory, antioxidant, antiangiogenic, anticancer, antimicrobial, neuroprotective and immunomodulatory activities [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, most of these studies were performed in human cell lines or animal models [15][16][17][18][19][20]. Only a small number of studies utilized primary human cell cultures, for example, our previous study on immunomodulatory effects of a bibenzyl compound (4,5-dihydroxy-3,3´,4´-trimethoxybibenzyl) isolated from D. lindleyi Steud.…”
Section: Introductionmentioning
confidence: 99%